2023
DOI: 10.7150/ijbs.79913
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 promotes GSDMD-mediated NET release by maintaining the transcriptional activity of Stat3 in sepsis-associated encephalopathy

Abstract: Sepsis-associated encephalopathy (SAE), as shown as acute and long-term cognitive impairment, is associated with increased mortality of sepsis. The causative factors of SAE are diverse and the underlying pathological mechanisms of SAE remain to be fully elucidated. Multiple studies have demonstrated a crucial role of microglia in the development of SAE, but the role of neutrophils and neutrophil extracellular traps (NETs) in SAE is still unclear. Here, we firstly show that in murine sepsis model, neutrophils a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“… 288 In human septic neutrophils, GSDMD transcription is regulated by STAT3, which involves nuclear PD-L1 translocation. 289 STAT3 also regulates the transcription of GSDMC, a process that necessitates the participation of nuclear PD-L1. Upon macrophage-derived TNF-α activation, caspase-8 cleaves GSDMC at the D365 site, generating GSDMC-NT, which ultimately leads to pyroptosis.…”
Section: Regulation Of Gasderminsmentioning
confidence: 99%
See 1 more Smart Citation
“… 288 In human septic neutrophils, GSDMD transcription is regulated by STAT3, which involves nuclear PD-L1 translocation. 289 STAT3 also regulates the transcription of GSDMC, a process that necessitates the participation of nuclear PD-L1. Upon macrophage-derived TNF-α activation, caspase-8 cleaves GSDMC at the D365 site, generating GSDMC-NT, which ultimately leads to pyroptosis.…”
Section: Regulation Of Gasderminsmentioning
confidence: 99%
“… 52 In addition, our team demonstrated the deleterious role of GSDMD-mediated NET release in sepsis-associated encephalopathy (SAE), and neutrophil-specific GSDMD knockout reduced plasma and hippocampal NET levels as well as ameliorated inflammatory injury in a murine model of SAE. 289 Neutrophil PD-L1 can be translocated to the nucleus, aided by the help of p-Y705-STAT3, to constitute the nPD-L1/p-Y705-STAT3 complex, which promotes the transcription of GSDMD. Consequently, they and we propose that therapeutically targeting GSDMD to directly inhibit NETosis, or targeting upstream regulators of GSDMD to indirectly inhibit NETosis, may represent an efficacious strategy for the treatment of sepsis.…”
Section: Gasdermins and Diseasesmentioning
confidence: 99%
“…While enhanced PD-L1 expression following surgical brain injury (SBI) can regulate neuroimmune and inflammatory responses through PD-L1 + astrocytes for self-protection and promote nerve repair, the opposite effect occurs in brain injury caused by sepsis ( 148 ). Our previous data showed that during sepsis, PD-L1 binds to P-Y705-Stat3, promoting nuclear translocation of PD-L1 and enhancing the transcription of GSDMD, resulting in increased release of neutrophil extracellular traps (NETs) ( 149 ). Neutrophils and NETs contribute to blood-brain barrier breakdown in the hippocampus, neuronal apoptosis, microglia activation, and hippocampal-dependent memory impairment ( 150 153 ).…”
Section: Role Of Pd-l1-mediated Intracellular Signaling In Sepsis-ind...mentioning
confidence: 99%
“…Neutrophils and NETs contribute to blood-brain barrier breakdown in the hippocampus, neuronal apoptosis, microglia activation, and hippocampal-dependent memory impairment ( 150 153 ). Treatment with anti-Gr-1 antibodies or DNase I has been shown to attenuate these sepsis-induced changes ( 149 ).…”
Section: Role Of Pd-l1-mediated Intracellular Signaling In Sepsis-ind...mentioning
confidence: 99%
See 1 more Smart Citation